Sports law - Thornton, Patrick K. (Jones and Bartlett Publishers, 2011)
The business of sports has become a multi-million dollar industry with legalities in sports leading the way. Sports Law looks at major court cases, statutes, and regulations that explore a variety of legal issues in the sports industry. The early chapters provide an overview of sports law in general terms and explore its impact on race, politics, religion, and everyday affairs. Later chapters address hot button issues such as gender equity, drug testing, and discrimination.